2022
DOI: 10.1111/pace.14466
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of bradyarrhythmia in patients with COVID‐19: Systematic scoping review

Abstract: COVID-19 has recently been associated with the development of bradyarrhythmias, although its mechanism is still unclear. We aim to summarize the existing evidence regarding bradyarrhythmia in COVID-19 and provide future directions for research.Following the PRISMA Extension for Scoping Reviews, we searched MEDLINE and EMBASE for all peer-reviewed articles using keywords including"Bradycardia," "atrioventricular block," and "COVID-19″ from their inception to October 13, 2021. Fortythree articles, including 11 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…A high incidence of arrhythmias was also reported in COVID-19 patients admitted to the intensive care unit, varying between ∼17%( 4, 65 ) and 44% ( 66, 67 ), with many patients displaying AV block, bradycardia and relative bradycardia( 6871 ), associated with worse prognosis( 70 ). In one study of COVID-19 patients with bradycardias, complete heart block was highly prevalent and pacemaker implantation was required in 76% of these cases( 72 ). Arrhythmias involving impaired CCS activity are also significantly increased in patients suffering from long COVID syndrome (also known as post-acute sequelae of COVID-19 or PASC).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A high incidence of arrhythmias was also reported in COVID-19 patients admitted to the intensive care unit, varying between ∼17%( 4, 65 ) and 44% ( 66, 67 ), with many patients displaying AV block, bradycardia and relative bradycardia( 6871 ), associated with worse prognosis( 70 ). In one study of COVID-19 patients with bradycardias, complete heart block was highly prevalent and pacemaker implantation was required in 76% of these cases( 72 ). Arrhythmias involving impaired CCS activity are also significantly increased in patients suffering from long COVID syndrome (also known as post-acute sequelae of COVID-19 or PASC).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, a worldwide survey reported that arrhythmias occurred in ~18% of COVID-19 patients (64), with the majority developing atrial arrhythmias (fibrillation or flutter), ~23% developing bradyarrhythmia (sinus pauses or AV block), and ~20% showing ventricular tachyarrhythmias (VT or VF). A high incidence of arrhythmias was also reported in COVID-19 patients admitted to the intensive care unit, varying between ~17%(4, 65) and 44% (66,67), with many patients displaying AV block, bradycardia and relative bradycardia (68)(69)(70)(71), associated with worse prognosis (70). In one study of COVID-19 patients with bradycardias, complete heart block was highly prevalent and pacemaker implantation was required in 76% of these cases (72).…”
Section: Cardiovascular Consequences Of Covid-19mentioning
confidence: 99%
“…We performed extensive search on MEDLINE and EMBASE for articles from the inception of the databases to February 20, 2022. We placed no filters for designs of studies and chief languages used as of our previous systematic review 17 . We also manually screened reference lists of every article to look for additional relevant articles using the reference lists that satisfied the eligibility criteria.…”
Section: Methodsmentioning
confidence: 99%
“…We placed no filters for designs of studies and chief languages used as of our previous systematic review. 17 We also manually screened reference lists of every article to look for additional relevant articles using the reference lists that satisfied the eligibility criteria. Our search strategy involved pertinent keywords including "marginal zone lymphoma," and "IgG4."…”
Section: Search Strategymentioning
confidence: 99%
“…Pacemaker insertion was needed in 76% of patients, and 46% required permanent cardiac implants. 64 Patients with COVID-19 with evidence of fevers, inflammation, and hypoxemia develop sinus tachycardia. 63 In a systematic review and meta-analysis of 19 studies including 33,296 hospitalized patients with COVID-19, the diagnosis of atrial fibrillation and/or atrial flutter was associated with poor clinical outcomes.…”
Section: Arrhythmiasmentioning
confidence: 99%